Surface Treatment of Concrete by Calcium Carbonate Biodeposition Using Candida orthopsilosis - Wong L.S.; Kong S.Y.; Oweida A.F.M.; Iqbal D.M.; Elhaddad E.A.E.; Regunathan P. (Jordan University of Science and Technology, 2023)
Adhesives; Beverages; Candida; Compressive strength; Contamination; Environmental protection; Geometry; Heavy metals; Seawater; Silica; Surface treatment; Water absorption; Yeast; Beverage industry; Biodeposition; Calcium carbonate crystals; Candida orthopsilosis; Construction chemicals; Contaminated concrete; Curing time; Eco-friendly; Epoxy; Leach ability; Leaching